2022
DOI: 10.3389/fgene.2022.1055396
|View full text |Cite
|
Sign up to set email alerts
|

Novel insight of N6-methyladenosine modified subtypes in abdominal aortic aneurysm

Abstract: Background: N6-methyladenosine (m6A) is the most prevalent non-cap reversible modification present in messenger RNAs and long non-coding RNAs, and its dysregulation has been linked to multiple cardiovascular diseases, including cardiac hypertrophy and atherosclerosis. Although limited studies have suggested that m6A modification contributes to abdominal aortic aneurysm (AAA) development, the full landscape of m6A regulators that mediate modification patterns has not been revealed.Methods: To distinguish the m6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Subsequently, we embarked on the development of a novel m6A-related gene signature AMRMS to forecast the progression of AAA. Previous studies have employed similar bioinformatics approaches to investigate the effects of m6A methylation on the progression or prognosis of AAA [9,[14][15][16][17]. However, these studies only analyzed the expression patterns of m6A modulators, but overlooked the analysis of m6A-modified RNAs, rendering their models for predicting the impact of m6A on AAA incompletely.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we embarked on the development of a novel m6A-related gene signature AMRMS to forecast the progression of AAA. Previous studies have employed similar bioinformatics approaches to investigate the effects of m6A methylation on the progression or prognosis of AAA [9,[14][15][16][17]. However, these studies only analyzed the expression patterns of m6A modulators, but overlooked the analysis of m6A-modified RNAs, rendering their models for predicting the impact of m6A on AAA incompletely.…”
Section: Discussionmentioning
confidence: 99%
“…AAA is characterized by vascular remodeling and progressive dilation ( 1 ), infiltration of lymphocytes and macrophages into the vessel wall, and smooth muscle cell apoptosis ( 108 ). Studies have revealed a significant increase in m6A modification levels in AAA, with elevated m6A posing an increased risk of AAA rupture ( 109 , 110 ). Moreover, differential expression of METTL14, FTO, and YTHDF3 has been observed in various types of inflammatory cells in AAA tissue.…”
Section: Epigenetic Mechanism Of Abdominal Aortic Aneurysmmentioning
confidence: 99%
“…The significance of m6A methylation in AAA has been reported, with abnormal m6A modification levels contributing to disturbed RNA metabolism and aberrant gene expression closely linked to AAA incidence and progression. 23 , 24 , 25 However, the correlation between m6A-SNPs and AAA risk in the human population remains unclear. Identifying AAA-associated m6A-SNPs through large-scale GWAS is crucial for understanding the genetic mechanisms underlying m6A modification in AAA pathogenesis and improving the fine mapping of causal variants.…”
Section: Introductionmentioning
confidence: 99%